2013
DOI: 10.1021/cb400159f
|View full text |Cite
|
Sign up to set email alerts
|

Two Related Pyrrolidinedione Synthetase Loci in Fusarium heterosporum ATCC 74349 Produce Divergent Metabolites

Abstract: Equisetin synthetase (EqiS), from the filamentous fungus Fusarium heterosporum ATCC 74349, was initially assigned on the basis of genetic knockout and expression analysis. Increasing inconsistencies in experimental results led us to question this assignment. Here, we sequenced the F. heterosporum genome, revealing two hybrid polyketide-peptide proteins that were candidates for the equisetin synthetase. The surrounding genes in both clusters had the needed auxiliary genes that might be responsible for producing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
106
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(107 citation statements)
references
References 37 publications
0
106
1
Order By: Relevance
“…Features of the gene products in the fsa cluster and its neighbors are summarized in Table 1 (GenBank: LC025956). The biosynthetic gene (eqx) cluster of 1 in Fusarium heterosporum ATCC 74349, which has been corrected recently [15], was very similar to the fsa cluster (Table 1).…”
Section: Identification Of the Biosynthesis Gene Cluster For 1 And 2 mentioning
confidence: 88%
“…Features of the gene products in the fsa cluster and its neighbors are summarized in Table 1 (GenBank: LC025956). The biosynthetic gene (eqx) cluster of 1 in Fusarium heterosporum ATCC 74349, which has been corrected recently [15], was very similar to the fsa cluster (Table 1).…”
Section: Identification Of the Biosynthesis Gene Cluster For 1 And 2 mentioning
confidence: 88%
“…Some PKS's, however, have an inactive ER domain; thus, final reduction of carbon-carbon double bonds along the carbon skeleton are achieved though collaboration with a trans-acting ER as observed in the biosynthesis of lovastatin [6,7], betaenone [8], and equisetin [9]. After decalin formation and subsequent chain elongation and modification, the resulting decalin polyketide product can be released from the PKS by various mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…After decalin formation and subsequent chain elongation and modification, the resulting decalin polyketide product can be released from the PKS by various mechanisms. A terminal PKS reduction domain catalyzes release in the betaenone and equisetin biosynthesis pathway [8,9], while a trans-acting thioesterase (LovG) is involved in the lovastatin pathway [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Computational analysis of the [4+2] cycloaddition with a truncated substrate indicated that the enzyme accelerates the cycloaddition a 1000-fold at 30°C. 25,26 Homologous genes are also found in the biosynthetic gene clusters of the tetramic acid-containing adducts such as equisetin (Eqx3; 90% identity) 27 and pyrrolocin (gNR600; 37%) 28 and macrocyclic adduct cytochalasin (CcsF; 27%). 29 Frequent occurrence of DAase genes with PKS-NRPS genes suggested co-evolution of these genes.…”
Section: Intramolecular Daases Generating Decalin Skeletonsmentioning
confidence: 99%